Economic mechanisms of encouraging of «green» economy in Kazakhstan (Eurasian Journal of Ecology, 2016)
In today's economy there are ideas about the interchangeability and interoperability of types of capital, this implies that a reduction of one type of capital may be to some extent offset by the increase of the other. Inthe twentieth century, developed countries are actively "replaced" natural capital, other types of capital, primarily physical (man-made), and human. In the article the basic economic mechanisms to encourage the development of "green" economy. Also presented are the main recommendations on measures of gradual transition to "green" the rails.
Keywords: the "green" economy; Kazakhstan; and economic mechanisms